Can we explain AMS-02 antiproton and positron excesses simultaneously by nearby supernovae without pulsars or dark matter?. (11th February 2016) - Kohri, Kazunori; Ioka, Kunihito; Fujita, Yutaka; Yamazaki, Ryo
Abstract: We explain the excess of the antiproton fraction recently reported by the AMS-02 experiment by considering collisions between cosmic-ray protons accelerated by a local supernova remnant and the surrounding dense cloud. The same "pp collisions" provide the right ratio of daughter particles to fit the observed positron excess simultaneously in the natural model parameters. The supernova happened in relatively lower metallicity than the major cosmic-ray sources. The cutoff energy of electrons marks the supernova age of 10^5 years, while the antiproton excess may extend to higher energy. Both antiproton and positron fluxes are completely consistent with our predictions in an earlier paper [Y. Fujita et al., Phys. Rev. D 80, 063003 (2009) [arXiv:0903.5298 [astro-ph.HE]]].